STATINS DRUG USE AND DRUG-DRUG INTERACTIONS - Maria Caecilia N.Setiawati; Caecilia Mutiarawati; Uswatun Chasanah; Lina Fatin Fauziyyah (Universitas Wahid Hasyim Semarang, 2020)
ABSTRACT Dyslipidemia is the commonest cause of many atherosclerotic diseases. Statins are the mainstay of the management of dyslipidemia, and it is widely prescribed for patients in Indonesia. This study aims to give an overview, the use of statin, and its drug-drug interactions. The study method was descriptive, using a purposive sampling technic. The inclusion criteria were patients who received statins therapy, in the outpatient installation of Tugurejo Regional Public Hospital, Semarang, during April 2017. There were 334 patients meet the inclusion criteria, most of them were women (63,28%). The highest patients’ range was 60-69 years old of 129 patients (38,62%). One hundred and thirty-one patients (39,22%) were diagnosed with dyslipidemia only. The dosage range of simvastatin and rosuvastatin was 10 to 20 mg once daily, but rosuvastatin was only given 10 mg once daily. The most dose was 10 mg simvastatin per day, prescribed for 231 patients (69,16%). There were 177 patients (52,99%) who has the potentiate of statin drug interactions. The most were simvastatin-amlodipine interactions, occurs in 104 patients (31,14%). This study shows that most statin users are elderly patients. Statin is used not only in dyslipidemia patients. There are many potential statin drug-drug interactions, but the statin dose is low and not over the standard doses. Keyword: dyslipidemia, statins, drug interactions